The Relationship of Special Education Placement and Academic Outcomes in Southeast Louisiana - Wolsefer, Brandie; Stedrak, Luke (Advances in Social Sciences Research Journal, 2025)
Special education placement is a debate amongst parents, educators, and policymakers. The Least Restrictive Environment (LRE) is a federal law that provides a guiding principle to assist the Individualized Education Plan (IEP) team guidance when considering placement for a student with an exceptionality. Student placement decisions affect school administrators, teachers, parents, and students. The purpose of the mixed methods study was to determine if students with disabilities who were taught in the inclusive setting yielded higher standardized test scores compared to students who were taught in the resource setting. The researcher analyzed the standardized test scores, in the areas of English Language Arts of fourth grade elementary school special education students, excluding the classification of gifted, talented students, and Intellectual Disability-Severe, in southeast Louisiana that participate in the inclusive and resource settings to discover which group of students yielded higher percentage gains. This study favored a quantitative approach that was structured to draw specific, data-driven conclusions about the relationship between student placement and academic achievement. This study also acknowledges that factors such as gender, race, SES, and English proficiency can influence academic outcomes.